The association of ACTN3 R577X polymorphism with sports specificity in Japanese elite athletes - Akazawa, N.; Ohiwa, N.; Shimizu, K.; Suzuki, N.; Kumagai, H.; Fuku, N.; Suzuki, Y. (Biology of Sport, 2022)
The a-actinin-3 proteins regulate muscle function and are located in the Z-line of the fast skeletal muscle. A common null polymorphism of R577X in a-actinin-3 gene (ACTN3) results in its complete absence in fast-twitch muscles. The ACTN3 R577X polymorphism is associated with sprint/power performance in athletes. However, little is known about how this polymorphism impacts sports other than sprint/power-oriented sports in Japanese elite athletes. The aim of our study was to examine the association between ACTN3 R577X polymorphism and elite athlete status in various sports categorized as power/sprint, endurance, artistic, martial arts, and ball game sports. The subjects included 906 Japanese elite athletes and 649 Japanese controls. We analysed the genotype frequency of the ACTN3 R577X polymorphism in sprint/power (n = 120), endurance (n = 150), artistic (n = 45), martial arts (n = 94), and ball game (n = 497) sports athletes. A higher number of sprint/power athletes were R allele carriers compared to the controls, and the endurance and artistic athletes (OR = 1.69, 1.83, and 2.36, 95% CI: 1.02-2.79, 1.02-3.31, and 1.08-5.13, respectively). The frequency of RR genotype was higher in sprint/power, martial arts, and ball game sports athletes (OR = 1.61, 1.84, and 1.39, 95% CI: 1.04-2.50, 1.11-2.95, and 1.05-1.83, respectively) compared to control. Furthermore, there is a significant linear trend with increasing R allele according to athletic status (P for trend < 0.05). The ACTN3 R allele is positively associated with sports performance requiring explosive power such as sprint/power, martial arts, and ball game sports categories.